2007
DOI: 10.1007/s00403-007-0745-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of substance P and its receptor neurokinin-1 in psoriasis and their relation to chronic stress and pruritus

Abstract: Substance P and its receptor(R) neurokinin (NK)-1 may have a role in the pathogenesis of psoriasis. Stress has been reported to play a role in the onset and exacerbation of psoriasis, which might include the substance P-NK-1 receptor(R) pathway. A feature of psoriasis, that has been correlated to the severity of stress and secretion of substance P, is pruritus. The objective of this study was to investigate the expression of substance P and the NK-1R in involved and noninvolved psoriatic skin, using a biotinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
2
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 28 publications
1
54
2
7
Order By: Relevance
“…Use of biotinylated SP suggested that NK-1 expression may be increased in keratinocytes from psoriatic plaques (71). Another study showed mast cells express the NK-1 receptor in both affected and unaffected psoriatic skin (6). NK-1 is also important in stress-induced murine skin mast cell activation (3,16), and in the development of atopic dermatitis in mice (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of biotinylated SP suggested that NK-1 expression may be increased in keratinocytes from psoriatic plaques (71). Another study showed mast cells express the NK-1 receptor in both affected and unaffected psoriatic skin (6). NK-1 is also important in stress-induced murine skin mast cell activation (3,16), and in the development of atopic dermatitis in mice (68).…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptides (5), especially SP, could be involved in the pathogenesis of inflammatory skin disorders, such as psoriasis (6,7), characterized by increased epidermal vascularization, keratinocyte hyperproliferation, and inflammation (8). SP-positive nerve fibers are more dense in psoriatic lesions and have an increased number of mast cell contacts compared with normal skin (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…A kilenc, alapkortizolszintet vizsgáló tanulmányból öt alacsonyabb plazma-vagy nyálhormon-koncentrációt mutatott ki [16,53,54,55,56,57,58,59,60]. Tudva, hogy a HPA-tengely működését és így a kortizoltermelést fokozó IFN-γ, TNF-α, IL-10, IL-12 és IL-18 plazmaszintjei emelkedettek pikkelysömörben, a megfi gyelt alacsony stresszhormon-koncentráció diszfunkcionális HPA-tengely-működést sejtet [61].…”
Section: A Hypothalamo-hypophyseo-adrenalis éS a Sympathyco-adrenomedunclassified
“…SP, one of the stress neuropeptides, is suggested to have a role of neurogenic inflammation in the pathogenesis of psoriasis. Expression of SP and its receptor correlated with the severity of depression and was associated with low level of cortisol, which indicates chronic stress (Remröd C et al, 2007;Amatya et al, 2011). SP also play a critical role in stressinduced mast cell degranulation in mice .…”
Section: Psoriasismentioning
confidence: 99%